Assessment of forest road models in concession areas in the Brazilian amazon - Morais, Pricila do Prado (2023)
Forest management aimed at the sustainable use of forest resources is an alternative land use to deforestation and can improve forest conservation in tropical regions. The construction of forest infrastructure, including forest roads, skid trails, and log-landings, is a key factor in minimizing the impacts and forest disturbances typically caused by selective logging activities in tropical forests. In this study, we used field and secondary data to assess the planned and implemented forest infrastructure in a study site of 5723 hectares under a forest concession in the Caxiuanã National Forest, located in the state of Pará, Brazilian Amazon. We tested alternative modeling approaches (the Tomlin and Spanning Tree models) by comparing them with the previously planned and implemented logging infrastructure by a concessionaire timber company (CEMAL Ltd.) in the study site. Our results indicate that the Tomlin model was the best approach for allocating forest roads in the study area, as it demonstrated the optimal balance between financial costs and forest disturbances for timber extraction. Additionally, Minimum Spanning Tree modeling achieved the most favorable results in delineating secondary roads and skid trails in the study site, despite slightly higher financial costs compared to the minimum acceptable costs. This alternative approach to modeling forest infrastructure can contribute to reducing forest disturbances and increasing the economic and ecological sustainability of forest management in tropical forests.